REVITALIZATION OF CORRECTIONAL ORGANIZATIONS: CURRENT DEVELOPMENT OF CORRECTIONAL SYSTEM IN INDONESIA - Alma Qarnain; Nathalina Naibaho (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2021)
Criminalization in Indonesia has changed its philosophy from